Efficacy and Safety of Shenqisuxin Granule for Non-ST-segment Elevation Acute Coronary Syndrome: Study Protocol for a Randomized, Double-Blinded, Placebo-Controlled Trial - Wu, Xiaoping; Guo, Ming; Shi, Shihua; Shi, Shengnan; Deng, Yanping; Wang, Shenglan; Wang, Yabing; Wang, Peili; Chen, Keji (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The Chinese herbal compound formula, Shenqisuxin granule (SQSX), promotes neovascularization and prevents in-stent restenosis in modern pharmaceutical studies and is expected to provide an effective strategy for non-ST-segment elevation acute coronary syndrome (NSTEACS). Thus, this study aims to examine the efficacy and safety of SQSX for NSTEACS and initially reveal its mechanism. Methods/Design: The study is a randomized, double-blinded and placebo-controlled trial. A total of 66 participants will be randomly allocated to one of the following two groups. Participants in the SQSX group will receive conventional treatment plus SQSX, while the placebo group will receive conventional treatment plus placebo, both for 14 days. The primary outcome, hs-CRP, and secondary outcome the Seattle Angina Questionnaire (SAQ) will be assessed at baseline,7±3days and 14±3days. At all visit windows, other indicators including creatine kinase(CK), creatine kinase-myocardial band (CK-MB), cardiac troponins I(cTnI), 12-lead electrocardiograph and the syndrome scores of Qi deficiency and blood stasis will be tested and metagenomic sequencing for intestinal flora will be performed. Echocardiography and safety assessment will be performed at baseline and 14±3days. Adverse events will be monitored during the trial. Discussion: The purpose of the study is to examine the efficacy and safety of SQSX to improve NSTEACS and initially reveal its mechanism.